(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Without the development of media literacy, social network users will remain trapped in a whirlpool of manipulative information, critical thinking will not develop, and their scope of thinking and worldview will gradually weaken. This article discusses the role and necessity of media literacy in the 21st century.